Moda, forestierismi e traduzioni: un confronto interlinguistico - Stefano Ondelli (Lingue Culture Mediazioni, 2021)
This paper deals with the presence of foreign words in magazines and websites regarding the fashion industry. After illustrating recent research aimed at assessing the frequency of loan words in Italian fashion magazines and classifying them according to a range of semantic fields, a survey is conducted on fashion magazines published in different countries to evaluate which language is more prone to accept loans and calques. As a third step, the different linguistic versions of the websites of American, French and Italian fashion brands are compared to assess whether differences emerge in the frequency and types of foreign words included in texts originally written in a given language vs. translated webpages. Despite the latest developments in the communication strategies of the fashion industry, the frequency and types of foreign words remain unchanged in both source and target texts and point to the persuasive and connotative – rather than denotative – role played by fashion terminology.